Advanced diagnostics applied to a self-breathing fuel cell - Obeisun,OA; Meyer,Q; Robinson,J; Gibbs,CW; Kucernak,AR; Shearing,P; Brett,DJL (2014)
In a self-breathing fuel cell, oxygen is taken directly from ambient air which provides the benefit of reduced system complexity and system operation. This study explores the use of, printed circuit boards (PCBs) as flow field plates to design a self-breathing fuel cell which helps reduce overall volume and cost of the system. It investigates the effect opening ratios have on fuel cell performance using polarization curves and electrochemical impedance spectroscopy. The result obtained indicates that greater opening ratios improve the mass transport properties of the fuel cell but increased Ohmic resistance as a result of the increased openings and reduced area of lands/ribs respectively. A maximum power density of 188 mW cm-2 was achieved.